Toward workforce integration: enhancements in adaptive behaviors and social communication skills among autistic young adults following vocational training course - Lousky, Yael; Selanikyo, Efrat; Tubul-Lavy, Gila; Ben-Itzchak, Esther (Frontiers in Psychology, 2024)
Background Cognitively able autistic adults demonstrate low rates of employment due to social and vocational challenges. The current study aimed to examine changes in various areas among autistic young adults who participated in the ‘Roim Rachok’ (‘Looking Ahead’ in Hebrew) Training Course (RRTC). The course prepares young autistic adults for integration into military service as vocational soldiers. Methods The study included 49 autistic participants who completed the RRTC in one of three vocational fields: Digital (n = 19), Technical (n = 9), and Visual (n = 21). Evaluations at the beginning and end of the course included adaptive behavior (Adaptive Behavior Assessment Scale 2nd Edition [ABAS-II]), autism symptom severity (Social Responsiveness Scale 2nd Edition [SRS-II]), and communication skills (Faux Pas; Empathy Quotient [EQ]; Friendship Quality Scale; Conversation task based on Yale in vivo Pragmatic Protocol [YiPP]). Results The results revealed a significant Time effect for the self-reported ABAS-II conceptual, social, and practical subdomains, EQ empathy quotient subdomain, Faux Pas, and SRS-II social communication interaction scores. Accordingly, participants reported increasing their adaptive skills, emotional empathy, and the ability to detect and interpret awkward statements, and decreased in their social communication interaction symptoms, following the RRTC. No significant Time x Group interaction was found for any of the examined measures, meaning similar trends were observed in all three vocational groups. Conclusion Following the RRTC, participants reported significant improvements in areas essential for their future integration as soldiers in the military and as employees in the vocational world. Implications of the study findings are discussed.